Michael Oriard on NCAA Academic Reform: Academics Over Dollars - Shropshire, Kenneth L. (Journal of Intercollegiate Sport, 2012)
The purpose of this paper is to provide a response to Michael Oriard’s keynote address. The paper highlights the link between monies generated through intercollegiate athletics and calls for academic reforms. There is also need for examination of how increased participant diversity coincided and influenced these dynamics—a connection frequently overlooked.